Self Directed Learning Improves Pancasila Education Outcomes in Elementary Students: Pembelajaran Mandiri Meningkatkan Hasil Pendidikan Pancasila pada Siswa Sekolah Dasar - Indah Sanabila; Machful Indrakurniawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Improving learning outcomes in elementary education remains a central priority for developing students’ academic competence and character formation. Specific Background: In Pancasila Education classes at Singogalih State Elementary School, many fourth-grade students showed low achievement and passive participation under conventional teacher-centered instruction. Knowledge Gap: Limited classroom-based evidence exists on how Self-Directed Learning (SDL) can address low mastery levels in primary civic education contexts. Aims: This study aimed to improve students’ learning outcomes through the implementation of the Self-Directed Learning model. Results: Using Classroom Action Research conducted in two cycles, the percentage of students meeting the Minimum Completion Criteria increased from 30.43% in the pre-cycle to 56.52% in Cycle I and 91.30% in Cycle II, accompanied by higher student activity, motivation, and deeper understanding of the material. Novelty: The study demonstrates a structured application of SDL in elementary Pancasila Education with measurable classroom-level gains across iterative cycles. Implications: The findings indicate that student-centered autonomous learning can serve as a practical instructional alternative for primary schools seeking to raise achievement while fostering independence and critical thinking skills. Highlights: Mastery rates rose from less than one-third of the class to over nine-tenths after two cycles. Learners became more active, motivated, and engaged during instruction. Autonomous goal setting and self-evaluation supported deeper content comprehension. Keywords: Self-Directed Learning; Learning Outcomes; Elementary Education; Pancasila Education; Classroom Action Research